22nd Digital Avionics Systems Conference Proceedings (Cat No 03CH37449) DASC-03 2003
DOI: 10.1109/dasc.2003.1245907
|View full text |Cite
|
Sign up to set email alerts
|

Effects of traffic display size and location on visual separation during visual approaches: Cockpit Display of Traffic Information (CDTI) Enhanced Flight Rules (CEFR)

Abstract: At many busy airports maximum efficiency and minimum delay occur when visual approaches are being conducted by pilots using visual separation from traffic for a portion of the approach. Pilot willingness to accept responsibility for visual separation also affords controllers maximum flexibility in traffic management under conditions of high traffic load. It may be possible to extend that efficiency to lower weather conditions if pilots are able to perform the same separation tasks by reference to a Cockpit Dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
1
1
0
Order By: Relevance
“…These results are comparable to the results reported in [7][8][9][10][11] where the operations concept required visual acquisition before the display could be used for spacing judgments. Pilots indicated that they were comfortable using the display to enable the delegated task, but did note in debriefing that they were assuming the displayed positions were accurate and that an appropriate level of certification for the equipment was in place.…”
Section: Feasibilitysupporting
confidence: 94%
See 1 more Smart Citation
“…These results are comparable to the results reported in [7][8][9][10][11] where the operations concept required visual acquisition before the display could be used for spacing judgments. Pilots indicated that they were comfortable using the display to enable the delegated task, but did note in debriefing that they were assuming the displayed positions were accurate and that an appropriate level of certification for the equipment was in place.…”
Section: Feasibilitysupporting
confidence: 94%
“…The concepts were referred to initially as CDTI Enhanced Flight Rules (CEFR) and then the more descriptive CDTI Assisted Visual Separation (CAVS). MITRE performed a series of human in the loop simulations [8][9][10][11][12] of a limited, delegated separation concept which started in visual meteorological conditions (VMC), with transitions through a cloud layer or other visibility restriction resulting in instrument meteorological conditions (IMC) of limited duration, until the aircraft broke out underneath the cloud layer. The CEFR/CAVS concept required the crew to first identify the reference traffic using direct visual contact, and then correlate the target with its representation on the CDTI.…”
Section: Delegated Separation Researchmentioning
confidence: 99%